Transition Metals in Organic Synthesis, Part 100: Highly Efficient Palladium(II)-Catalyzed Oxidative Cyclization to the 1,7,8-Trioxygenated Carbazole Alkaloid Murrayastine - Huet, Laurent; Forke, Ronny; Jäger, Anne; Knölker, Hans-Joachim (Synlett, 2012)
Consecutive palladium-catalyzed C–N and C–C bond formation provides an efficient route to the 1,7,8-trioxygenated carbazole alkaloid murrayastine.
Keywords: alkaloids; catalysis; cyclization; palladium